CM CHONDRITES EXHIBIT THE COMPLETE PETROLOGIC RANGE FROM TYPE 2 TO 1 - Zolensky M.E.; Mittlefehldt D.W.; Lipschutz M.E.; Wang M.S.; Clayton R.N.; Mayeda T.K.; Grady M.M.; Pillinger C.; Barber D. (My University, 1997)
We have characterized the most phyllosilicate-rich members of the CM chondrite group. Based upon petrographic and compositional factors, we conclude that these particular meteorites have experienced pervasive aqueous alteration far beyond that witnessed by typical CMs. The lack of anhydrous silicates, CAI and (except as relicts) chondrules merits the classification of type CMI for three meteorites (EET 83334, ALH 88045, and one Kaidun lithology). Still other CMs, notably ALH 83100, EET 90047, and Yamato 82042, are clearly intermediate between types 1 and 2. Brecciated CM chondrites like Cold Bokkeveld contain all of these varied lithologies. The CM chondrites thus exhibit the complete petrologic range from 2 through 1. Our results show that progressive aqueous alteration on the parent CM asteroid(s) was, locally, accompanied by significant increases in temperature (to a peak of ∼450°C for the Kaidun lithology), fO2, and (locally) degree of chemical leaching, all well beyond the conditions recorded by typical CM2s. The most altered CMs also are commonly deformed, displaying a distinct lineation probably due to static rather than dynamic forces.